Assessing engineering exercises: a novel taxonomy. Issue 17 (2022) - Liotino, Marica; Garone, Anja; Knorn, Steffi; Varagnolo, Damiano; Garone, Emanuele; Fedeli, Monica
Abstract: Formally describing and assessing the difficulty of learning and teaching material is important for quality assurance in university teaching, for aligning teaching and learning activities, and for easing communications among stakeholders such as teachers and students. We propose a novel taxonomy to describe and quantify the difficulty levels of exam questions and exercises encountered in engineering-related contexts, together with its development and piloting processes. The taxonomy consists of two dimensions which separately and independently describe the difficulty in understanding / explaining and using / applying a content unit. The piloting phase included 10 purposefully selected experts in the field of control engineering, external to the project, that tested its performance, utility, ease of use, and clarity. The results indicate that the users were able to provide consistent and coherent assessments of the difficulty levels of 15 selected exam questions. The paper further discusses suggestions for improvement voiced by the participants in order to promote an even more consistent and coherent assessment of engineering students' mastery of the subject.